Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1471-0528.2010.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of decidual insulin‐like growth factor binding protein‐1 in cervical fluid in early and mid‐pregnancy are associated with an increased risk of spontaneous preterm delivery

Abstract: Objective To study whether elevated levels of decidual insulin-like growth factor binding protein-1 (IGFBP-1) in the cervical fluid of unselected asymptomatic women in early or mid-pregnancy are associated with spontaneous preterm delivery (PTD).Design Prospective population-based cohort study.Setting Maternity Clinics, University Central Hospital, Helsinki, Finland.Population A total of 5180 unselected pregnant women.Methods Cervical swab samples were collected during the first and second trimester ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Rahkonen et al found that the CVF phIGFBP-1 level of ≥10 ug/l predicts PTL with sensitivities varying from 40.0% to 89.5% and NPVs from 90% to 100% [24]. Rahkonen et al concluded that the elevated phIGFBP1 level in the first trimester was an independent predictor of spontaneous PTL, especially < 32 gestational weeks [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahkonen et al found that the CVF phIGFBP-1 level of ≥10 ug/l predicts PTL with sensitivities varying from 40.0% to 89.5% and NPVs from 90% to 100% [24]. Rahkonen et al concluded that the elevated phIGFBP1 level in the first trimester was an independent predictor of spontaneous PTL, especially < 32 gestational weeks [24].…”
Section: Discussionmentioning
confidence: 99%
“…Rahkonen et al concluded that the elevated phIGFBP1 level in the first trimester was an independent predictor of spontaneous PTL, especially < 32 gestational weeks [24].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of IGF-1R in normal and pathological growth and differentiation and aging involve interactions with the ubiquitous growth factors, hormones, and proinflammatory cytokines that are considered to be mediators of the labor process [33][35]. Several IGF-binding proteins that regulate IGF-1R–dependent signaling cascades have been studied in the context of SPTB, and some of them have been implicated in preterm labor [36][38]. However, these studies did not involve IGF1R and thus the extension of studies involving IGF-1R (particularly the ligand-binding alpha subunit encoded by exons 1–10) to the process of labor, with special consideration of fetal involvement in the endocrine and paracrine control of the preterm labor process, is clearly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies provided data on cervicovaginal phosphorylated insulin-like growth factor binding protein-1 (phI-GFBP-1), [65][66][67]69,[72][73][74]77,79 seven studies provided data on relaxin, 34,60,61,70,71,75,78 three studies provided data on cervicovaginal human chorionic gonadotrophin (hCG), 63,68,76 two studies provided data on cervicovaginal prolactin, 62,64 four studies provided data on pregnancy-associated plasma protein-A (PAPP-A), 81,84,85,87 two studies provided data on activin-A, 80,82 and one study each provided data on placental protein-13 (PP13) 83 and pregnancy-specific-b1 glycoprotein (SP1). 86 For cervicovaginal levels of hCG, phIGFBP-1, and prolactin, the pooled sensitivities, specificities, positive and negative LRs to predict preterm birth before 32, 34, and 37 weeks of gestation ranged between 33 and 83% (median, 67%), 62 and 97% (median, 79%), 1.6 and 19.0 (median, 3.2), and 0.2 and 0.8 (median, 0.5), respectively (Table 1).…”
Section: Placental Protein/hormone-related Biomarkersmentioning
confidence: 99%